1972
DOI: 10.1002/bjs.1800590406
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-hour liver preservation in the pig using hypothermia and hyperbaric oxygen

Abstract: In an attempt to prolong successful storage of the pig liver beyond the 6–8 hours previously described from this laboratory, the addition of cell‐membranestabilizing drugs to the preserving solution and the use of a potassium‐rich solution were investigated. Using simple hypothermia alone, 10‐ and 12‐hour storage was unsuccessful. Using the previously described hypothermic technique, but with the addition of hyperbaric oxygen at 3 atmospheres absolute (A.T.A.), consistently successful 12‐hour preservation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…et al 6 reported that in vitro cultures of adult rat liver required a higher oxygen tension for maintenance, which indicated that hyperbaric oxygen might improve injury of organ preservation. Furthermore, Slapak, M. et al 7 and Spilg, H. et al 8 successfully preserved animal livers for 24 hours under three atmospheres of oxygen and hypothermia. Another in vitro study showed that HBOT during liver cold storage protected against subsequent hepatic reperfusion injury by attenuating oxidant stress and the depletion of energy loss, such as ATP 9 .…”
Section: Hbot In Acute Liver Injurymentioning
confidence: 99%
“…et al 6 reported that in vitro cultures of adult rat liver required a higher oxygen tension for maintenance, which indicated that hyperbaric oxygen might improve injury of organ preservation. Furthermore, Slapak, M. et al 7 and Spilg, H. et al 8 successfully preserved animal livers for 24 hours under three atmospheres of oxygen and hypothermia. Another in vitro study showed that HBOT during liver cold storage protected against subsequent hepatic reperfusion injury by attenuating oxidant stress and the depletion of energy loss, such as ATP 9 .…”
Section: Hbot In Acute Liver Injurymentioning
confidence: 99%
“…In vivo experiments showed the 6-hour preserved liver displayed good concentration of Tc 99m and excretion of bile, but these functions were poor in 12-hour preserved liver. In 1972, Spilg et al (1972 investigated the pig liver preservation of hypothermia with and without HBO in a potassium-rich solution, and their results showed 10-and 12-hour storage was unsuccessful using simple hypothermia alone (2-5°C), but 12-hour preservation was successfully achieved with the addition of HBO at 300 kPa. Tran et al (2012) found HBO could attenuate the ischemia, preservation and reperfusion injury in a rat model of liver transplantation (reductions in apoptosis, necrosis and serum alanine transaminase).…”
Section: Effects Of Hbo On Organ Preservationmentioning
confidence: 99%
“…The details of these various simple techniques are summarized elsewhere. 2,4,18,19 Short interval simple hypothermic preservation techniques have had extensive trials in man in both Denver and England with the shipment of livers from city to city. The Cambridge-Kings College group have used a plasma solution for cold infusion of homografts, 38 while the Denver group have used Collins solution.…”
Section: Liver Preservationmentioning
confidence: 99%